Relaxed secant-type methods - Argyros, Ioannis K; Magreñán, Á. Alberto (Nonlinear Studies, 2018)
We present a unified local and semilocal convergence analysis for secant-type methods in order to approximate a locally unique solution of a nonlinear equation in a Banach space setting. Our analysis includes the computation of the bounds on the limit points of the majorizing sequences involved. Under the same computational cost, using both Lipschtiz and center Lipschitz conditions, our convergence criteria can be: weaker; the error bounds more precise and the convergence balls larger than in earlier studies. Special cases such us Newton's method or Secant method are also presented. Numerical examples, including a Chandrasekhar equation and a boundary value problem, are also presented to illustrate the theoretical results obtained in this study.
Keywords: banach space; divided difference; local convergence; majorizing sequence; secant-type method; semilocal convergence; Scopus